Identifikasi Bukti Digital WhatsApp pada Sistem Operasi Proprietary Menggunakan Live Forensics - Riadi, Imam; Sunardi, Sunardi; Rauli, Muhamad Ermansyah (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Negeri Semarang, 2018)
Rapid development of computer technology is also accompanied with increasing of cybercrime. One of the most common crimes is fraud case in the online shop. This crimeÃ‚Â abuses Whatapps, one of the most popular Instant Messenger (IM) applications.Ã‚Â WhatsApp is one of the IM applications that can be used on computers, especially on windows 8.1 operating system. All applications running on the computer leave data and information on Random Access Memory (RAM). The data and information that exist in RAM can be obtained using digital forensic technique calledLive Forensics. Live forensics can be used when the computer is running and connected to theÃ‚Â network. This research aims to find digital evidence related to online shop fraud case. The digital evidence can be obtained using one of the forensic tools FTK Imager. FTK Imager can retrieve and analyze data and information on RAM. The results obtained in this research is the content of WhatsApp conversations that can be used as digital evidence to reveala fraud in the online shop.